Bis(perfluoropinacolato)silane: a neutral silane Lewis superacid activates Si-F bonds - Tschernuth, Florian; Thorwart, Thaddäus; Greb, Lutz; Hanusch, Franziska-Maria; Inoue, Shigeyoshi (Angewandte Chemie. International edition, 2021)
Despite the earth abundance and easy availability of silicon, only few examples of isolable neutral silicon centered Lewis superacids are precedent in the literature. To approach the general drawbacks of limited solubility and unselective deactivation pathways, we introduce a Lewis superacid, based on perfluorinated pinacol substituents. The compound is easily synthesized on a gram-scale as the corresponding acetonitrile mono-adduct 1⋅(MeCN) and was fully characterized, including single crystal X-ray diffraction analysis (SC-XRD) and state-of-the-art computations. Lewis acidity investigations by the Gutmann-Beckett method and fluoride abstraction experiments indicate a Lewis superacidic nature. The challenging Si−F bond activation of Et3SiF is realized and promising catalytic properties are demonstrated, consolidating the potential applicability of silicon centered Lewis acids in synthetic catalysis.
Zuerst veröffentlicht: 27 September 2021
Gesehen am 05.10.2022